Yeast and mammalian metallothioneins functionally substitute for yeast copper-zinc superoxide dismutase. - Tamai, K T (1993)
Copper-zinc superoxide dismutase catalyzes the disproportionation of superoxide anion to hydrogen peroxide and dioxygen and is thought to play an important role in protecting cells from oxygen toxicity. Saccharomyces cerevisiae strains lacking copper-zinc superoxide dismutase, which is encoded by the SOD1 gene, are sensitive to oxidative stress and exhibit a variety of growth defects including hypersensitivity to dioxygen and to superoxide-generating drugs such as paraquat. We have found that in addition to these known phenotypes, SOD1-deletion strains fail to grow on agar containing the respiratory carbon source lactate. We demonstrate here that expression of the yeast or monkey metallothionein proteins in the presence of copper suppresses the lactate growth defect and some other phenotypes associated with SOD1-deletion strains, indicating that copper metallothioneins substitute for copper-zinc superoxide dismutase in vivo to protect cells from oxygen toxicity. Consistent with these results, we show that yeast metallothionein mRNA levels are dramatically elevated under conditions of oxidative stress. Furthermore, in vitro assays demonstrate that yeast metallothionein, purified or from whole-cell extracts, exhibits copper-dependent antioxidant activity. Taken together, these data suggest that both yeast and mammalian metallothioneins may play a direct role in the cellular defense against oxidative stress by functioning as antioxidants.